2010
DOI: 10.1103/physrevc.82.044901
|View full text |Cite
|
Sign up to set email alerts
|

Coupling relativistic viscous hydrodynamics to Boltzmann descriptions

Abstract: Models of relativistic heavy ion collisions typically involve both a hydrodynamic module to describe the high density liquid-like phase and a Boltzmann module to simulate the low density breakup phase which is gas-like. Coupling the prescriptions is more complicated for viscous prescriptions if one wants to maintain continuity of the entire stress-energy tensor and currents. Derivations for the viscosity for a gas are reviewed, which then lead to expressions for changes in the phase space occupation based on s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 45 publications
1
97
0
Order By: Relevance
“…For example, in the context of Grad's quadratic ansatz that is usually employed at freeze-out, this occurs when the nonequilibrium correction to the distribution function is comparable-or exceeds-the equilibrium one. In the context of relativistic heavy-ion collisions numerous hydrodynamic simulations (usually with temperature-independent η/s) have shown that large enough means η/s ∼ 0.3-0.5 [10,13,50,75,[77][78][79][80]. For larger values of η/s it is not possible to match the predictions of hydrodynamic models to RHIC data.…”
Section: -5mentioning
confidence: 99%
“…For example, in the context of Grad's quadratic ansatz that is usually employed at freeze-out, this occurs when the nonequilibrium correction to the distribution function is comparable-or exceeds-the equilibrium one. In the context of relativistic heavy-ion collisions numerous hydrodynamic simulations (usually with temperature-independent η/s) have shown that large enough means η/s ∼ 0.3-0.5 [10,13,50,75,[77][78][79][80]. For larger values of η/s it is not possible to match the predictions of hydrodynamic models to RHIC data.…”
Section: -5mentioning
confidence: 99%
“…The extent of the simulation in the transverse direction was confined to a radius of R = 40 fm, with an extra buffer distance set up to ensure that the existence of the boundary could not affect the particles with radius r < R during the finite time over which the cascade ran. The initial momentum distribution was modified to reproduce arbitrary initial π zz using the techniques of [43]. The distribution of the particles longitudinally was confined to spatial rapidities −η s,min < η < η smax , with cyclic boundary conditions to longitudinal boosts.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…The initial momenta were chosen according to the prescription in [43]. This code was modified relative to previous versions to initially generate particles with a distribution of masses consistent with a thermal-weighted modified Lorentzian distribution.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…However, because collisions between two tracer particles is neglected, the list of interactions is abbreviated and given in Eq. (13). For a collision between incoming particles whose momenta, position and charges are labeled by p 1 and p 2 while the outgoing particles are denoted by q 1 , · · · q M , the cascade must consider three cases.…”
Section: Methods For Accounting For Backflowmentioning
confidence: 99%
“…Viscous corrections can be applied according to [13]. This involves transforming the momentum according to (in the rest frame)…”
Section: Appendix: Algorithm For Generating Particlesmentioning
confidence: 99%